The Use of Beetroot Juice as an Impregnating Solution to Change Volatile Compounds, Physical Properties and Influence the Kinetics of the Celery Drying Process - Magdalena Kręcisz; Marta Klemens; Aleks Latański; Bogdan Stępień (Molecules, 2024)
The effect of different methods of drying celery root enriched with beet juice by vacuum impregnation (VI) was studied. The process of convection drying, vacuum drying and freeze drying was carried out. Compared to dried indigenous celery, dry impregnated tissue was characterized by lower values of dry matter, L* and b* color parameters, as well as higher values of water activity, density and a* color parameter. In addition, VI reduced the drying time. Forty Volatile Organic Compounds (VOCs) were found in celery, while fifty-one VOCs were found in the profile of celery with beetroot juice. The innovative method of vacuum impregnation made it possible to produce a new type of product with changed properties and a variable VOCs profile. The best fit of the drying process kinetics was achieved by using the logistic model. Increasing the temperature during convection drying resulted in shorter drying time, increased values of dry matter, reduced the water activity value and altered VOCs.